ANÁLISIS DE SATISFACCIÓN DEL CLIENTE DEL GRAND HOTEL LOJA - Apolo Oviedo, Jefferson Andrés (2022)
The objective of this research work is to analyze the degree of customer satisfaction based on the services offered by the Grand Hotel Loja, in order to fulfill this general objective, three specific ones were proposed: analyze the level of quality in services and infrastructure offered by the Grand Hotel Loja, know the level of customer satisfaction based on the service received at the Grand Hotel Loja and propose strategies to improve the services of the Grand Hotel Loja. For the first objective: to analyze the level of quality of services and infrastructure offered by the Grand Hotel Loja, the methodology of a self- qualification of lodging services was used, where it was obtained as a result that the hotel infrastructure complies with the desired expectations by guests, this allows customers to feel their stay pleasant and guarantee the loyalty of the hotel, thus maximizing the use of economic resources that is the main objective of any company. For the second objective: to know the level of customer satisfaction based on the service received at the Gran Hotel Loja, the Servqual methodology was used, where it was obtained that 93% of the customers rated the services provided during their stay at the hotel as very satisfactory, that is to say, the level of customer satisfaction was rated as very satisfactory. For the third objective: to propose strategies to improve the services of the Grand Hotel Loja, an adapted methodology of Quito was used, which resulted in eight strategies that will significantly improve the services offered by the hotel. Likewise, implementing the strategies proposed in this project will help the company to obtain continuous improvement and achieve the goals proposed by the hotel.